TỔNG HỢP VÀ THỬ HOẠT TÍNH SINH HỌC CỦA MỘT SỐ DẪN CHẤT ARYLOXY-S-TRIAZIN - Thanh Hải, Đinh Thị; Trang, Hoàng Thu (Vietnam Journal of Chemistry, 2012)
By the reaction of cyanuric chloride with various phenols in the presence of NaOH as a catalyst compound 1 - 6 was obtained. The structures of synthesized compounds were confimed by IR, 1H-NMR, 13C-NMR and mass spectroscopy. The obtained compounds had been investigated on biological activity such as antifungal activity, antibacterial activity and cytotoxic activity. Keywords: Aryloxy-s-triazin, cyanuric chloride, biological activity.